Harnessing the potency of eco-friendly calcium oxide derived from eggshells for enhanced photocatalytic activity and biocompatibility evaluation in HepG2 cell line - V. Bhuvaneshwari; S. Sonia; D. Sivaganesh (Chemical Physics Impact)
Efforts towards sustainable development and pollution prevention are driving the exploration of bio-Calcium oxide (CaO) production from eggshell waste. This work investigates the thermal conversion of eggshell derived CaCO3 into CaO. Powder X-ray diffraction and Fourier transform infrared spectroscopy confirm CaO composition, displaying a cubic structure with 2.405 Å bond length and a mid-bond electron density of 0.2298 e/Å³. Electron density studies corroborate this, revealing a three-dimensional distribution and one-dimensional profile. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirms spherical CaO particles and EDAX spectra displays the presence of calcium and oxygen. UV absorption spectra reveal a 3.3 eV energy bandgap, showcasing CaO's photocatalytic potential. It demonstrates exceptional photocatalytic against congo red and methylene blue dyes, degrading them by 96.4 % and 98 %, respectively, via pseudo first-order kinetics. Additionally, CaO demonstrates promising anticancer activity against HepG2 liver cancer cells, with an IC50 value of 31.2 μg/mL, positioning it as a cost-effective and potent agent for both wastewater treatment and cancer therapy.